Respostas de híbridos de meloeiro amarelo à restrição hídrica - Rodrigues, Amadeus Mozarth Gomes (2021)
The cultivation of melon in Brazil takes place under irrigation, with a predominance of localized irrigation system. The improvement in the efficiency of water use will come from the delivery of the necessary quantity for the plant to have its best productive performance. On the other hand, understanding the mechanisms and responses that plants have in the face of water restriction will enable the development of hybrids with greater efficiency in the use of water. In this sense, the present study aimed to evaluate the growth, gas exchange and nutritional status of different hybrids of yellow melon cultivated under water restriction. The experiment was conducted in a greenhouse, belonging to Embrapa Agroindustry Tropical, Fortaleza - CE, in the period from October to December 2019. The experimental design was in a factorial 4x4, arranged in random blocks, being evaluated four hybrids of yellow melon ( Dali, Gladial, Goldex and Natal) and four irrigation depths (40; 60; 80 and 100% of the crop evapotranspiration, ETc). The following variables were evaluated: number of leaves, length of the main branch, stem diameter and leaf gas exchange (photosynthesis, transpiration and stomatal conductance), leaf area, dry leaf mass, stem, roots and total, fruit mass and state nutritional. Plant growth and development was reduced by increased water restriction, although at the end of the cycle there were no differences between hybrids. The gas exchange of yellow melon hybrids was affected by treatments of irrigation levels, with a decrease in photosynthetic efficiency at more restrictive levels. There was a variation in the nutritional status of yellow melon hybrids in terms of N, P, K, Ca, S and Mg, which showed a tendency to grow with increasing levels of irrigation.